Forms, folds, sizes : all the details graphic designers need to know but can never find - Evans, Poppy, 1949- (Rockport Publishers, 2008)
"It's tough to remember all the minute details of packaging standards and conversions when you are a designer juggling varied projects. With Forms, Folds, and Sizes - Second Edition, you can just look them up! Including updated information and new topics, this handbook provides designers with all the little details that can make or break a design, such as how much space to leave in the gutter when designing barrel folds, how to layout a template for a box and the ratios of each part, metric conversion charts, and standard envelope sizes in the USA, Europe, Canada, and Asia." "Featuring new topics such as sustainable design, web design, and grid design basics, Forms, Folds, and Sizes - Second Edition is the one resource to turn to for answers to everything from folds and bindings to paper, imaging, and much, much more!" "Poppy Evans is an award-winning writer and graphic designer. She is the former art director of Screen Printing and American Music Teacher magazines, and former managing editor of HOW magazine."--Jacket